A Fuzzy Improved ACO Approach for Test Path Optimization (International Journal of Engineering and Computer Science, 2015)
To improve the software reliability it is required to test each aspect of software system. But sometime, the testing also increases the cost and time of software release. Because of this, it is required to execute the only the effective test cases undere some controlled mechanism. In this paper, a fuzzy improved ACO approach is defined to generate the optimized test path. To assign the weightage to test cases, the module interaction analysis and fault analysis are used collectively in this work. The experimentation is performed on some real time programs. The results shows that the proposed approach has reduced the overall test cost cost of software system